Terminal Maastrichtian ammonites from the Cretaceous-Paleogene Global Stratotype Section and Point, El Kef, Tunisia - Goolaerts, S; Kennedy, W; Dupuis, C; Steurbaut, E (2004)
Ammonites are described for the first time from the terminal Maastrichtian in the Cretaceous-Paleogene (K/P) Global Stratotype Section and Point at El Kef, Tunisia. A rich assemblage, consisting of at least 17 taxa, occurs in the interval from 7 to 2 m below the K/P boundary. They co-occur with a diverse macrofauna, which also includes rudists. All fossils are pyritic, and the ammonites are all nuclei, mostly <20 mm in diameter. The dominance of Indoscaphites suggests open connections with southern India along the southern Tethys. No ammonites have been recovered from the 2-m interval below the K/P boundary in the Tunisian basin, although other macrofossil groups, including some originally aragonitic bivalve taxa, persist up to the boundary and are also present in the basal Paleogene. © 2004 Elsevier Ltd. All rights reserved.